Життєвий та творчий шлях М.Н. Шуста на матеріалах фондового зібрання Ніжинського краєзнавчого музею ім. І. Спаського - Рой, С.В. (Сіверщина в історії України, 2021)
У статті представлені результати дослідження та аналізу
документальної спадщини відомого письменника, педагога, громадського діяча Миколи Шуста, які зберігаються у відділі фондів
НКМ ім. І. Спаського та перебувають на стадії науково-технічного опрацювання. Вивчення особових документів М. Шуста дає
можливість здійснити переосмислення у сьогоденних реаліях життєвого та творчого шляху письменника, презентувати оновлене
бачення значення даної постаті в історії Ніжина та Ніжинщини. The article presents the results of research and analysis of the documentary
heritage of the famous writer, teacher, public figure Mykola
Shust, which are stored in the department of funds of the NKM nnnamed
after I. Spasskyi and are at the stage of scientific and technical
development. The study of M. Shust’s personal documents gives an opportunity
to rethink the current realities of the writer’s life and creative
path, to present an updated vision of the significance of this figure in
the history of Nizhyn and Nizhyn region.
Today, scientists are not interested in studying the life and creative
heritage of prominent figures of science and culture of the twentieth
century, which is designed to clarify their role in the social and
cultural life of Ukraine. One of the most famous figures of educational
and socio-cultural space of the Nizhyn region in the second half of
the twentieth century was Mykola Naumovych Shust - a teacher, writer,
publicist and public figure.
Studying the source base, represented by personal documents, works
of M.N. Shust, stored in the funds of the NCM named after I. Spasskyi,
managed to find out the main stages of his life and career: 1940-1960
- a period of active teaching; 1970 - early 2000’s - a period marked by
active creative work of M.N. Shust. The talented teacher made a significant
contribution to the education of many generations of young people
from Nizhyn. As a public figure, he was a popularizer of Ukrainian
culture during the Second World War, being in an underground organization.
In his autobiographical works, the writer continued the ancient
literary traditions of Nizhyn Higher School.